Health impact assessment of the UK soft drinks industry levy: a comparative risk assessment modelling study - Dr Adam D M Briggs, MFPH; Oliver T Mytton, MPH; Ariane Kehlbacher, PhD; Prof Richard Tiffin, PhD; Ahmed Elhussein, BA; Prof Mike Rayner, DPhil; Prof Susan A Jebb, PhD; Prof Tony Blakely, PhD; Peter Scarborough, DPhil (Elsevier, 2017)
Background: In March, 2016, the UK Government proposed a tiered levy on sugar-sweetened beverages (SSBs; high tax for drinks with >8 g of sugar per 100 mL, moderate tax for 5-8 g, and no tax for <5 g). We estimate the effect of possible industry responses to the levy on obesity, diabetes, and dental caries. Methods: We modelled three possible industry responses: reformulation to reduce sugar concentration, an increase of product price, and a change of the market share of high-sugar, mid-sugar, and low-sugar drinks. For each response, we defined a better-case and worse-case health scenario. We developed a comparative risk assessment model to estimate the UK health impact of each scenario on prevalence of obesity and incidence of dental caries and type 2 diabetes. The model combined data for sales and consumption of SSBs, disease incidence and prevalence, price elasticity estimates, and estimates of the association between SSB consumption and disease outcomes. We drew the disease association parameters from a meta-analysis of experimental studies (SSBs and weight change), a meta-analysis of prospective cohort studies (type 2 diabetes), and a prospective cohort study (dental caries). Findings: The best modelled scenario for health is SSB reformulation, resulting in a reduction of 144 383 (95% uncertainty interval 5102-306 743; 0·9%) of 15 470 813 adults and children with obesity in the UK, 19 094 (6920-32 678; incidence reduction of 31·1 per 100 000 person-years) fewer incident cases of type 2 diabetes per year, and 269 375 (82 211-470 928; incidence reduction of 4·4 per 1000 person-years) fewer decayed, missing, or filled teeth annually. An increase in the price of SSBs in the better-case scenario would result in 81 594 (3588-182 669; 0·5%) fewer adults and children with obesity, 10 861 (3899-18 964; 17·7) fewer incident cases of diabetes per year, and 149 378 (45 231-262 013; 2·4) fewer decayed, missing, or filled teeth annually. Changes to market share to increase the proportion of low-sugar drinks sold in the better-case scenario would result in 91 042 (4289-204 903; 0·6%) fewer adults and children with diabetes, 1528 (4414-21 785; 19·7) fewer incident cases of diabetes per year, and 172 718 (47 919-294 499; 2·8) fewer decayed, missing, or filled teeth annually. The greatest benefit for obesity and oral health would be among individuals aged younger than 18 years, with people aged older than 65 years having the largest absolute decreases in diabetes incidence. Interpretation: The health impact of the soft drinks levy is dependent on its implementation by industry. Uncertainty exists as to how industry will react and about estimation of health outcomes. Health gains could be maximised by substantial product reformulation, with additional benefits possible if the levy is passed on to purchasers through raising of the price of high-sugar and mid-sugar drinks and activities to increase the market share of low-sugar products. Funding: None.